Exploring the Therapeutic Potential of Cannabidiol in U87MG Cells: Effects on Autophagy and NRF2 Pathway - Laura Giannotti; Benedetta Di Chiara Stanca; Francesco Spedicato; Daniele Vergara; Eleonora Stanca; Fabrizio Damiano; Luisa Siculella (Antioxidants)
Cannabinoids include both endogenous endocannabinoids and exogenous phytocannabinoids, such as cannabidiol (CBD), and have potential as therapeutic agents in cancer treatment due to their selective anticancer activities. CBD exhibits both antioxidant and pro-oxidant effects depending on its concentration and cell types. These properties allow CBD to influence oxidative stress responses and potentially enhance the efficacy of antitumor therapies. In this study, we treated U87MG glioma cells with low dose (1 μM) CBD and evaluated its molecular effects. Our findings indicate that CBD reduced cell viability by 20% (p < 0.05) through the alteration of mitochondrial membrane potential. The alteration of redox status by CBD caused an attempt to rescue mitochondrial functionality through nuclear localization of the GABP transcription factor involved in mitochondria biogenesis. Moreover, CBD treatment caused an increase in autophagic flux, as supported by the increase in Beclin-1 and the ratio of LC3-II/LC3-I. Due to mitochondria functionality alteration, pro-apoptotic proteins were induced without activating apoptotic effectors Caspase-3 or Caspase-7. The study of the transcription factor NRF2 and the ubiquitin-binding protein p62 expression revealed an increase in their levels in CBD-treated cells. In conclusion, low-dose CBD makes U87MG cells more vulnerable to cytotoxic effects, reducing cell viability and mitochondrial dynamics while increasing autophagic flux and redox systems. This explains the mechanisms by which glioma cells respond to CBD treatment. These findings highlight the therapeutic potential of CBD, suggesting that modulating NRF2 and autophagy pathways could represent a promising strategy for glioblastoma treatment.